Sacrifical sites, types and function - Vorren, Örnulv (Scripta Instituti Donneriani Aboensis, 1987)
Much has been written and said about Saami mythology and pre-Christian religion. There is, however, considerably less documentation of concrete cultural elements in scholarly descriptions. These investigations are considered important not only because they aim to provide documentation that can be used for studies of Saami mythology and pre-Christian religion. They also provide material that can throw light on the function of the holy places in a social context through analysis of their origin, their connections with certain families and persons, their associations with the siidas, their location within the areas where the Saamis from these siidas gained their livelihood, etc. The materials collected about the sacrificial sites also play an important role in studying the course of events leading up to the differentiation of Saami hunting and gathering culture. A question that has frequently arisen in the course of this work is with what powers or deities the different sacrificial sites were associated. This is naturally connected with their origin and their form. This, in turn, is reflected in the traditions and legends recounted concerning them. It is also reflected in their location in the physical environment and in the kinds of offerings that have been found. In the materials so far collected it is possible to distinguish between about eight different types of sacrificial site and holy mountain or fell according to their form and location: holy fells, rock formations, stone boulders, holes, cracks in fells, springs, lakes, ring-shaped sacrificial sites. Missionaries were urged to destroy the offering sites.